Emotion and memory in development biological, cognitive, and social considerations - Quas, Jodi A.; Fivush, Robyn (Oxford : Oxford University Press, 2009)
This title explores stress and memory, neurobiology, stress effects on the brain system underlying explicit memory relationships and stress, and much more.
Includes bibliographical references and index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Memory in children; Emotions in children; Child psychology